On-Job Communicative Competencies of Dentists in Pondicherry - Dr.T. Pushpanathan; K. Narasimma Bharathi (UICELL, 2022)
Globalization nowadays has significantly influenced the activity and endurance of organizations around the world; the business of dentistry has not been resistant. Dentists are the people who have to deal with various individuals during their practice, have to explain the treatment plans, instructions if any to the patients, and so on. Patients with multicultural backgrounds would need to be explained in the common connecting language; in India English is the connecting language. The difficulties faced by the dentists are that they are fluent in medical terms but have to be trained appropriately to explain in layman's terms to the patients for their better understanding in a place like Pondicherry (the study area) have patients from other countries also as it is one among the few places of Dental Tourism in India. Apart from this, there is no separate course in English prescribed for dental students in India. The General English Course which the students study till their senior secondary schooling would not be sufficient to understand a language like English and communicate. A Specific English course has to be the need of the hour for Dental students so that it could be useful and prepare them for their professional excellence. Hence, a study of this kind aims to identify the required communicative competencies for Dentists in practice. The findings will help in deciding the required skill sets for the recommendation of the ESP curriculum prescribed for Dentists. Keywords: communication, competencies, ESP, dentists, curriculum, etc.